Could anemia be the reason for dysfunctional cognition??? - Kharat, Pranali S.; Waghmare, Pradnya P. (International Journal of Research in Medical Sciences, 2017)
Background: Studies claim that anemia at any time in life can hamper the metabolic processes and subsequently affect the cognitive and behavioral domain of an individual. Late-adolescent girls are one of the most vulnerable groups due to commencement of menstrual cycles, hormonal changes, nutritional deficits etc. It is also the time period where adolescents enter their professional careers in our country where cognition forms the basis of all the learning. This study was focused on seeing whether anemia affects the P300 wave which is a cognitive evoked potential. Methods: 74 girls of first and second year MBBS were chosen for this study. They were divided into two groups on basis of hemoglobin estimation by cyanmethemoglobin method. A comparative study was done of P300 latency and P300 amplitude between the two groups. Results: Comparison between the anemic group to the control group revealed: Latency of P300 was significantly delayed in the anemic group and amplitude was significantly higher in the control group. Conclusion: The results suggested a better cognitive performance of those having normal hemoglobin levels.